Small mammals in the diet of barn owls (Tyto alba) in agroecosystems of southern Brazil - Scheibler, D. R.; Christoff, A. U. (Neotropical Ornithological Society, Usgs Patuxent Wildlife Research Center, 2004)
We studied the diet of the Barn Owl (Tyto alba) in an agricultural area of southern Brazil (29degrees36'S, 52degrees11'W), based on analysis of regurgitated remains. The results clearly showed that the diet of the Barn Owl reflects the human impact on its habitat. The cosmopolitan house mouse (Mus musculus) was the most preyed upon small mammal (81.9%) and the most important in terms of the Barn Owl ingested biomass (69%). This rodent, due to its small size, is also responsible for the relatively low me-an weight off small mammal prey in the owl diet (19.6 g). In southern Brazilian agroecosystems, the Barn Owl probably feeds mainly on mice due to their great abundance in crop fields and grain storage areas of the region.
Keywords: barn owl; Tyto alba; predation; Mus musculus; agrosystems; Brazil